Situational breakdowns understanding protest violence and other surprising outcomes - Nassauer, Anne 1982- (New York Oxford University Press, 2019)
"In our everyday lives, we rely on routines that make tasks and interactions easier and provide a sense of order - routines of greeting each other, getting to work, organizing the things we do on the job, at the gym, or during family dinners. Yet, we have all experienced situations where routines fail and people behave contrary to expectations. In Situational Breakdowns, Anne Nassauer demonstrates that when routines break down, surprising outcomes often emerge. Focusing on detailed accounts of peaceful and violent protests from the 1960s until 2010, violent uprisings such as Ferguson 2014, and armed store robberies caught on CCTV, Nassauer argues that by systematically looking at the way situations unfold, clear patterns can be identified for how and why routine interactions break down. Employing over 1,000 visual recordings, documentary sources, interviews with participants, and participant observation with police, she shows which factors can draw us into violent situations and discusses how and why we make uncommon individual and collective decisions. Drawing on insights from sociology, psychology, primatology, international relations, and neuroscience, Nassauer compares situational dynamics with human motivations to demonstrate that our interactions, interpretations, and emotions greatly influence the outcome of situations. A novel interpretation of surprising social outcomes, Situational Breakdowns reveals that, despite the course of events overriding motivations, people can avoid being caught up in violence, if they know what to look for."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Demonstrations; Political violence; Protest movements; Riots